Metal ceramic inert anode with high electric conductivity and heat conductivity and high-temperature molten salt corrosion resistance and preparation method of metal ceramic inert anode

By introducing SiC and ZrB2 ceramics into aluminum electrolytic anode materials, the component ratio is optimized, and the problem of difficult balance of conductivity and corrosion resistance of anode materials in high-temperature molten salts is solved, and the comprehensive performance of the anode and the purity of the primary aluminum are significantly improved. .

CN119462117AActive Publication Date: 2025-02-18CENT SOUTH UNIV

Patent Information

Application Number
CN202411607393.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing aluminum electrolytic anode materials have problems in the high-temperature molten salt corrosion, which leads to serious anode corrosion and affects electrolytic efficiency and product quality.

Method used

By introducing SiC and ZrB2 ceramics, the component proportion of NiFe2O4-NiO cermet inert anode is optimized, and its electrical conductivity and thermal resistance to high-temperature molten salt corrosion are improved.

Benefits of technology

It significantly improves the conductivity and corrosion resistance of the metal cermet inert anode, slows down the corrosion rate of the anode, ensures the high purity of primary aluminum, and solves the problem of corrosion of traditional anode materials in high-temperature molten salts.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a metal ceramic inert anode with high electric conductivity and heat conductivity and high-temperature molten salt corrosion resistance and a preparation method of the metal ceramic inert anode. According to the method, a ceramic component ZrB2 (the conductivity is 1 * 104 S / cm to 1.2 * 105 S / cm) with good electrical conductivity and a ceramic component SiC (the heat conductivity coefficient is 320 W / m.K to 348 W / m.K) with good heat conduction performance are introduced, so that the (Cu) Ni metal content in the NiFe2O4-NiO-based metal ceramic is reduced, the electric conduction and heat conduction performance of the metal ceramic inert anode is improved, meanwhile, the molten salt corrosion resistance of the inert anode is improved, the annual corrosion rate is 0.64 cm / y or below, and the metal ceramic inert anode can be applied to the field of metal ceramics. The cathode primary aluminum also has relatively high purity, and the purity reaches 99.7% or above; the method is easy to operate, efficient and beneficial to application and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum electrolysis, and in particular to a NiFe2O4-NiO-SiC-ZrB2-based high-conductivity thermal-electrical high-temperature molten salt corrosion-resistant metal ceramic inert anode and a preparation method thereof. Background Art

[0002] In the aluminum electrolysis process, the performance of anode materials has a crucial impact on electrolysis efficiency, cost and product quality. Traditional anode materials have many shortcomings. For example, in order to achieve a balance between density, mechanical properties, electrical and thermal conductivity, and high-temperature molten salt corrosion resistance, NiFe2O4-NiO-based metal ceramic inert anodes often increase the Cu (Ni) metal content in NiFe2O4-NiO-based metal ceramics. This will cause the Cu (Ni) metal to corrode preferentially during the electrolysis process, resulting in a large number of micropores on the surface of the metal ceramic inert anode, providing a permeation channel for the high-temperature molten salt electrolyte, and the metal ceramic inert anode will be severely corroded. Although it is possible to add a certain amount of zirconium boride powder to the ceramic phase to replace the spinel oxide to slow down the oxide ceramic peeling phenomenon caused by the preferential corrosion of the metal phase in high-temperature molten salt (202110489130.6); or adopt a multi-layer prefabricated sintering method to control the metal phase content in the metal ceramic layer in contact with the electrolyte melt and the metal material in the area connected to the metal guide rod to improve the corrosion resistance of the anode (202410555733.5), it still has little effect on large-scale aluminum electrolysis.

[0003] As a material with high hardness, high thermal conductivity, good chemical stability and certain electrical conductivity, SiC has potential application value in the field of inert anode materials. The addition of SiC to the ceramic phase is conducive to the dissipation of heat and maintains the temperature stability of the anode during the electrolysis process. Compared with some metal phases, it has stronger corrosion resistance, can effectively resist the erosion of molten salt, and extend the service life of the anode.

[0004] The conductivity of ZrB2 ceramics is 1×10 4 ~1.2×10 5 S / cm, which is three orders of magnitude higher than the 10~100 S / cm conductivity of NiFe2O4-NiO. Adding ZrB2 ceramics can reduce the Cu (Ni) metal content in NiFe2O4-NiO-based metal ceramics, and can avoid the formation of a large number of holes on the anode surface due to preferential corrosion of Cu (Ni) metal, resulting in premature destruction of the anode.

[0005] The addition of ZrB2 and SiC ceramics can effectively improve the electrical and thermal conductivity and high temperature molten salt corrosion resistance of metal ceramic inert anodes; this method is simple to operate and efficient, which is conducive to industrial promotion and application. Therefore, an innovative preparation method is needed to give full play to the advantages of SiC and ZrB2 to obtain high-performance metal ceramic inert anodes. Summary of the invention

[0006] In view of the problems in the prior art of aluminum electrolysis inert anodes, such as rapid erosion of oxide ceramic grain boundaries by infiltrated electrolyte due to preferential corrosion of the metal phase, and local overheating of the electrode due to poor thermal conductivity, the purpose of the present invention is to provide a NiFe2O4-NiO-SiC-ZrB2-based highly conductive and thermally conductive high-temperature molten salt corrosion-resistant metal ceramic inert anode and a preparation method thereof. By reasonably introducing SiC and ZrB2 and optimizing the proportion of each component, the problems of the difficulty in balancing the conductive properties and molten salt corrosion resistance of the existing anode materials and the limitations of SiC when used alone are solved, the comprehensive performance of the anode is improved, the annual corrosion rate is reduced, and the high purity of the cathode raw aluminum is ensured.

[0007] In order to achieve the above technical objectives, the technical solution provided by the present invention is:

[0008] The present invention provides a high-conductivity, heat-conductivity, high-temperature molten salt corrosion-resistant metal ceramic inert anode for aluminum electrolysis. The metal ceramic inert anode material consists of a metal phase and a ceramic phase, wherein the metal phase consists of non-spinel oxide NiO, and the ceramic phase comprises ZrB2 ceramic, SiC ceramic, and NiFe2O4-based ceramic; the metal ceramic inert anode comprises the following components in mass percentage: spinel oxide NiFe2O4 40% to 90%, non-spinel oxide NiO 1% to 40%, SiC 1% to 20%, and ZrB2 1% to 10%.

[0009] The present invention adds ZrB2, a ceramic component with excellent electrical conductivity, and SiC, a ceramic component with excellent thermal conductivity, to a NiFe2O4-NiO metal ceramic inert anode, thereby reducing the Cu (Ni) metal content in the NiFe2O4-NiO-based metal ceramic, improving the electrical and thermal conductivity of the metal ceramic inert anode, and simultaneously improving the molten salt corrosion resistance of the inert anode.

[0010] In a preferred embodiment, the mass fraction of the spinel oxide NiFe2O4 in the metal ceramic inert anode material is 50-80wt%.

[0011] In a preferred embodiment, the mass fraction of the SiC ceramic phase in the metal ceramic inert anode material is 1-10wt%.

[0012] In a preferred embodiment, the mass fraction of the ZrB2 ceramic in the metal ceramic inert anode material is 5-10wt%.

[0013] In a preferred embodiment, the non-spinel oxide is NiO, and its mass fraction in the metal ceramic inert anode material is preferably 10-30wt%.

[0014] The method for preparing the highly conductive and heat conductive high temperature molten salt corrosion resistant metal ceramic inert anode comprises the following steps:

[0015] The raw materials NiFe2O4, NiO, SiC and ZrB2 powders are mixed and evenly milled in a ball mill according to a certain proportion; the mixed powders are cold pressed into an anode green body, and then the anode green body is sintered in an inert atmosphere to obtain the anode green body.

[0016] The above method is preferably as follows: the raw materials NiFe2O4, NiO, SiC and ZrB2 powders are uniformly mixed in a ball mill in proportion, with a ball-to-material ratio of 5:1~8:1, a rotation speed of 300~400r / min, and a ball milling time of 4~5h; the mixed powder is cold-pressed into an anode green body at a pressure of 150~200MPa, and then the anode green body is sintered in an inert atmosphere at 1200~1300℃ for 5~6h.

[0017] Preferably: the raw materials NiFe2O4, NiO, SiC and ZrB2 powders are mixed uniformly in a ball mill in proportion, with a ball-to-material ratio of 5:1, a rotation speed of 300r / min, and a ball milling time of 4h; the mixed powder is cold-pressed into an anode green body at a pressure of 200MPa, and then the anode green body is sintered in an inert atmosphere at 1300°C for 5h.

[0018] The electrolyte used in the electrolysis experiment includes Na3AlF6 and / or K3AlF6, AlF3, CaF2 and Al2O3. In a preferred embodiment, the electrolyte includes the following components in mass percentage: Na3AlF6 and / or K3AlF6 60-80%, AlF3 5-30%, CaF2 ≤ 10%, Al2O3 3-5%.

[0019] The technical principle of the present invention and the beneficial technical effects brought by it compared with the prior art:

[0020] Principle: A large number of studies have shown that under the temperature and current density of the present invention, ZrB2 ceramics with good electrical conductivity and SiC ceramics with good thermal conductivity are introduced together into a metal ceramic inert anode, and then placed in an appropriate electrolyte for electrolytic corrosion. Since there are fewer metal components in the metal ceramic inert anode, and ZrB2 ceramics have good electrical conductivity and SiC ceramics have good thermal conductivity, in the aluminum electrolysis process, the NiFe2O4-NiO-SiC-ZrB2-based metal ceramic inert anode will be compared with the NiFe2O4-NiO metal ceramic inert anode. The electrical conductivity, thermal conductivity and molten salt corrosion resistance are improved, and the anode corrosion rate can be effectively slowed down. At the same time, fewer anode components are dissolved in the electrolyte, and the amount of impurity metal generated by cathode discharge is also small, thereby maintaining the cathode original aluminum with a higher purity.

[0021] Beneficial effects: (1) The technical solution of the present invention can improve the electrical conductivity, thermal conductivity and corrosion resistance of the metal ceramic inert anode for aluminum electrolysis, and at the same time improve the purity of the original aluminum, solving the problems of the current NiFe2O4-NiO metal ceramic inert anode in the aluminum electrolysis process, such as the preferential corrosion of Cu (Ni) metal, which leads to the decrease of electrical conductivity and the need to improve the anode's resistance to molten salt corrosion. (2) The technical solution of the present invention is simple and convenient, and can be easily promoted and applied. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with the embodiments, but is not intended to limit the scope of protection of the claims of the present invention.

[0023] Example 1

[0024] The raw material powder mass fraction used in this embodiment is as follows: NiFe2O4 is 70%, NiO is 15%, SiC is 5%, and ZrB2 is 10%. The above raw material powders are mixed evenly in a ball mill, with a ball-to-material ratio of 5:1, a rotation speed of 300r / min, and a ball milling time of 4h. The mixed powder is cold-pressed into an anode green body under a pressure of 200MPa, and then the anode green body is sintered in an inert atmosphere at 1300℃ for 5h to obtain a 5(SiC) / 85(NiFe2O4-15NiO)-10ZrB2 metal ceramic inert anode.

[0025] The electrolyte used in the electrolysis experiment is a mixture of 78.07% Na3AlF6-9.5% AlF3-5.0% CaF2- 7.43% Al2O3 (primary crystallization temperature 947°C, superheat 13°C), the electrolysis temperature is 960°C, and the electrolysis time is 120h. According to the formula (W loss =W b ×C b +W a ×Ca )×106×365×24 / (S 阳极 ×ρ 阳极 ×t) (1)

[0026] In formula (1), W loss Defined as the annual anode corrosion rate (cm / year), W b is the total amount of electrolyte (g), C b is the impurity concentration entering the electrolyte (ppm), W a is the total amount of cathode aluminum (g), C a is the impurity concentration in the aluminum liquid entering the cathode (ppm), S anode is the surface area of ​​the anode immersed during electrolysis (cm 2 ), ρanode is the volume density of the anode (g / cm 3 ), t is the electrolysis time (h).

[0027] 5(SiC) / 85(NiFe2O4-15NiO)-10ZrB2 metal ceramic inert anode, its conductivity at 960℃ is 183.7S / cm; in electrolyte 78.07% Na3AlF6-9.5%AlF3-5.0%CaF2-7.43%Al2O3 (primary crystallization temperature 947℃, superheat 13℃, current density 1.0 A / cm 2 ) After 120h of electrolysis (electrolysis temperature 960 ℃), it was found that the corrosion rate of 5(SiC) / 85(NiFe2O4-15NiO)-10ZrB2 anode was 0.64 cm / year. The purity of the original aluminum was 99.7%, indicating that the introduction of SiC and ZrB2 can improve the high-temperature conductivity and high-temperature molten salt corrosion resistance of the metal ceramic inert anode.

[0028] Example 2

[0029] The conductivity of the 10(SiC) / 85(NiFe2O4-15NiO)-5ZrB2 metal ceramic inert anode at 960℃ is 168.2 S / cm; in the low-temperature electrolyte 78.07% Na3AlF6-9.5%AlF3-5.0%CaF2-7.43%Al2O3 (primary crystallization temperature 947℃, superheat 13℃, current density 1.0 A / cm 2 ) After 120h of electrolysis (electrolysis temperature 960 ℃), it was found that the corrosion rate of 10(SiC) / 85(NiFe2O4-15NiO)-5ZrB2 anode was 0.71 cm / year and the purity of the original aluminum was 99.6%.

[0030] Example 3

[0031] The conductivity of the 5(SiC) / 95(NiFe2O4-15NiO) metal ceramic inert anode at 960℃ is 52.5 S / cm; in the low-temperature electrolyte 78.07% Na3AlF6-9.5%AlF3-5.0%CaF2-7.43%Al2O3 (primary crystallization temperature 947℃, superheat 13℃, current density 1.0 A / cm 2 ) After 120h of electrolysis (electrolysis temperature 960 ℃), it was found that the corrosion rate of 5(SiC) / 95(NiFe2O4-15NiO) anode was 1.92cm / y and the purity of the original aluminum was 99.1%.

[0032] Example 4

[0033] The conductivity of the 10(SiC) / 90(NiFe2O4-15NiO) metal ceramic inert anode at 960℃ is 45.8 S / cm; in the low-temperature electrolyte 78.07% Na3AlF6-9.5%AlF3-5.0%CaF2-7.43%Al2O3 (primary crystallization temperature 947℃, superheat 13℃, current density 1.0 A / cm 2 ) After 120h of electrolysis (electrolysis temperature 960 ℃), it was found that the corrosion rate of 10(SiC) / 90(NiFe2O4-15NiO) anode was 2.32cm / y and the purity of the original aluminum was 98.5%.

[0034] Example 5

[0035] 5(20Ni-Cu) / 85(NiFe2O4-15NiO)-10ZrB2 metal ceramic inert anode has a conductivity of 145.2 S / cm at 960℃; in the electrolyte 78.07% Na3AlF6-9.5%AlF3-5.0%CaF2-7.43%Al2O3, (primary crystallization temperature 947℃, superheat 13℃, current density 1.0A / cm 2 ) After 120h of electrolysis (electrolysis temperature 960℃), it was found that the corrosion rate of 5(20Ni-Cu) / 85(NiFe2O4-15NiO)-10ZrB2 anode was 2.23 cm / year. The purity of the original aluminum was 98.7%.

[0036] Example 6

[0037] The conductivity of the 10(20Ni-Cu) / 85(NiFe2O4-15NiO)-5ZrB2 metal ceramic inert anode at 960℃ is 113.1 S / cm; in the electrolyte 78.07% Na3AlF6-9.5%AlF3-5.0%CaF2-7.43%Al2O3 (primary crystallization temperature 947℃, superheat 13℃, current density 1.0A / cm 2) After 120h of electrolysis (electrolysis temperature 960℃), it was found that the corrosion rate of 10(20Ni-Cu) / 85(NiFe2O4-15NiO)-10ZrB2 anode was 2.89 cm / year. The purity of the original aluminum was 98.3%.

[0038] Example 7

[0039] The conductivity of the 15(20Ni-Cu) / 85(NiFe2O4-15NiO) metal ceramic inert anode at 960℃ is 43.1 S / cm; in the electrolyte 78.07% Na3AlF6-9.5%AlF3-5.0%CaF2-7.43%Al2O3, (primary crystallization temperature 947℃, superheat 13℃, current density 1.0A / cm 2 ) After 120h of electrolysis (electrolysis temperature 960℃), it was found that the corrosion rate of 15(20Ni-Cu) / 85(NiFe2O4-15NiO) anode was 3.35 cm / year. The purity of the original aluminum was 97.4%.

Claims

1. A highly conductive and thermally conductive metal ceramic inert anode resistant to high temperature molten salt corrosion, comprising NiFe2O4, NiO, SiC and ZrB2.

2. The high-conductivity, heat-conductivity, high-temperature molten salt corrosion-resistant metal ceramic inert anode according to claim 1, characterized in that: The mass proportion of each component: NiFe2O4 40%~90%, NiO 1%~40%, SiC 1%~20%, ZrB2 1%~10%.

3. The high-conductivity, heat-conductivity, high-temperature molten salt corrosion-resistant metal ceramic inert anode according to claim 2, characterized in that: The mass proportion of each component is: NiFe2O4 50-80%, NiO 10-30%, SiC 1-10%, ZrB2 5-10%.

4. The method for preparing the high-conductivity, heat-conductivity and high-temperature molten salt corrosion-resistant metal ceramic inert anode according to claim 1, 2 or 3, characterized in that: The following steps are involved: The raw materials NiFe2O4, NiO, SiC and ZrB2 powders are mixed and evenly milled in a ball mill according to a certain proportion; the mixed powders are cold pressed into an anode green body, and then the anode green body is sintered in an inert atmosphere to obtain the anode green body.

5. The preparation method according to claim 4, characterized in that: The raw materials NiFe2O4, NiO, SiC and ZrB2 powders are mixed uniformly in a ball mill in proportion, with a ball-to-material ratio of 5:1~10:1, a rotation speed of 200~500r / min, and a ball milling time of 3~6h; the mixed powder is cold-pressed into an anode green body under a pressure of 100~300MPa, and then the anode green body is sintered in an inert atmosphere at 1100~1400℃ for 4~6h.

6. The preparation method according to claim 5, characterized in that: The raw materials NiFe2O4, NiO, SiC and ZrB2 powders are mixed evenly in a ball mill in proportion, with a ball-to-material ratio of 5:1, a rotation speed of 300r / min, and a ball milling time of 4h; the mixed powder is cold-pressed into an anode green body under a pressure of 200MPa, and then the anode green body is sintered in an inert atmosphere at 1300℃ for 5h.

Citation Information

Patent Citations

  • A highly corrosion-resistant cermet inert anode material for aluminum electrolysis and its preparation method.

    CN113186569B

  • Preparation method of inert anode

    CN118461075A

  • A method of fabrication of inert anodes

    CA3073388A1

  • Inert anode material for aluminium electrolysis and method for manufacturing same

    CN101255570A

  • High temperature resistant molten salt corrosion ceramet anode material and preparation method thereof

    CN101586246A

Cited By

  • A high-conductivity, high-heat-conductivity, high-temperature-molten-salt-corrosion-resistant metal ceramic inert anode and its preparation method

    CN119462117B